Production of fermented green tea and its nutrient analysis: a mini review - Rana, Prerna; Panda, Priyanka; Shukla, Priyanshi; Sahore, Ambika; Chauhan, Apoorva; Karnwal, Arun (Journal of Postharvest Technology, 2021)
The most consumed beverage world wide is tea and is grown by approximately more than 60 countries. There are a number of tea’s present in the market, out of which “fermented green tea” is one type. The fermented green tea is prepared by the fermentation of green tea leaves by using a consortium of microorganisms which can include bacterial and fungal species like Bacillus subtilis, Aspergillus oryzae, Pseudomonas savastanoi, Aspergillus lucheunsis etc. The use of different microorganism leads to different tastes, flavours and textures of the tea. Fermentation enhances the nutritional value of green tea like enhanced levels of polyphenols, flavonoids, catechins, some organic acids etc., and also offer a number of health benefits like reduction in obesity, lower blood pressure, helps in preventing breast cancer and a lot many other benefits. The following article describes the microbial composition, biochemical composition, and methods for the preparation of fermented green tea, effects of fermented green tea and the future prospects